The Use of maritime alphabet in Maritime English : A literature Review - Yusrah; Piping Rahadianto (English Lecturers and Teachers Association (ELTA), 2026)
Effective communication is a fundamental requirement in maritime operations, where clarity and accuracy are essential to ensuring safety at sea. One key element supporting this objective is the Maritime Alphabet, also known as the NATO phonetic alphabet, which standardizes oral communication among seafarers from diverse linguistic backgrounds. This literature review examines the role of the Maritime Alphabet in English language learning within maritime education contexts. The review analyzes 20 selected sources, including peer-reviewed journal articles, International Maritime Organization (IMO) conventions and guidelines, and Maritime English textbooks published between 2015 and 2024, drawing on pedagogical frameworks in English for Specific Purposes (ESP) and Maritime English. The findings indicate that integrating the Maritime Alphabet into Maritime English instruction enhances pronunciation accuracy, listening comprehension, and learners’ confidence in oral communication. Furthermore, its integration with the Standard Marine Communication Phrases (SMCP) supports the development of professional communicative competence required by international maritime standards. The literature also highlights that simulation-based, task-oriented, and blended learning approaches significantly improve cadets’ engagement and practical communication performance. Despite these benefits, challenges remain, including persistent pronunciation difficulties among non-native speakers, limited exposure to authentic communication contexts, and insufficient instructional resources. Overall, this review underscores the Maritime Alphabet as a core component of Maritime English pedagogy, contributing to the development of standardized communicative competence essential for safety and professionalism in maritime education. Keywords : Maritime Education; Phonetic Alphabet; Professional Communication